Ladder-type poly(indenofluorene-co-benzothiadiazole)s as efficient gain media for organic lasers: design, synthesis, optical gain properties, and stabilized lasing properties. Issue 26 (22nd June 2017) - Chang, Si-Ju; Liu, Xu; Lu, Ting-Ting; Liu, Yuan-Yuan; Pan, Jin-Qiang; Jiang, Yi; Chu, Shuang-Quan; Lai, Wen-Yong; Huang, Wei
Abstract : A novel set of ladder-type poly(indenofluorene- co -benzothiadiazole)s were designed, synthesized, and explored as efficient gain media for organic lasers. Abstract : A set of ladder-type poly(indenofluorene)s incorporating various indenofluorene chain lengths and 2, 1, 3-benzothiadiazole (BT) units, namely n LF-BT ( n = 2–4), have been designed, synthesized and explored as gain media for organic lasers. The thermal, photophysical, electrochemical, electroluminescence, and optical gain properties of the resulting polymers have been systematically investigated in comparison with those of their poly(9, 9-dioctylfluorene- co -benzothiadiazole) counterpart (F8BT ) to unravel the structure–property relationships. It was found that with an extension of the ladder indenofluorene chain length the resulting copolymers exhibited progressively enhanced optical and electrical properties with low ASE thresholds, high net gain coefficients, and boosted device efficiency. The BT units played a key role in inducing energy transfer that further stabilized the optoelectronic properties of the resulting copolymers. Single-emissive-layer organic light-emitting devices based on n LF-BT exhibited superior maximum luminance and current efficiency in comparison with those ofF8BT due to the incorporation of ladder-type indenofluorene chain structures. Solution-processed non-doped films exhibited prominent amplified spontaneous emission (ASE) and lasing characteristics. The ASE activity could still be detectable even upon annealing up to 280 °C for n LF-BT ( n = 2–4). In particular, a relatively low ASE threshold of 6.04 μJ cm −2 with an emission peak at 568 nm and a high optical gain coefficient of g = 84 cm −1 were recorded for 4LF-BT. Moreover, one-dimensional (1D) distributed feedback (DFB) lasers based on 4LF-BT achieved a rather low lasing threshold of 7.2 nJ pulse −1 (0.60 kW cm −2, 3.0 μJ cm −2 ), showing great promise as robust gain media for organic lasers. These results suggest that the novel copolymer design strategy incorporating indenofluorene and BT units is rather attractive to construct robust gain media with promising low thresholds, high net gain coefficients, and stabilized lasing properties for organic lasers.